Implementasi Keamanan Jaringan dengan Metode Whitelist pada Server Jurusan Elektro di Politeknik Negeri Malang - Januar Ariq Pratama (Politeknik Negeri Malang, 2019)
State Polytechnic of Malang is an educational institution based on technique where the database is needed here, the database itself is important data that must be stored and cannot be seen by others. Database security must be developed and prioritized so that no one breaks into important data on the server. This whitelist method utilizes a port that can block port access to outside networks that are vulnerable to criminal acts, this method uses ssh as a medium to manage control of an ip address. The ip address will be added a port behind it. Use IP block with Linux OS and tested via the web and laptop using a local access point. The test results show that the quality used for security is whitelist, where this method is used for the IP security used. IP block and unblock process can be done well. The process of adding and deleting ports can be done well. So that in general, the whole system is running well and easy access.